Serum levels of albumin‐amyloid beta complexes are decreased in Alzheimer's disease. Issue 3 (11th September 2013) - Yamamoto, Keiichi; Shimada, Hiroyuki; Koh, Hideo; Ataka, Suzuka; Miki, Takami
<x xml:space="preserve">Abstract</x> Aim Decreased amyloid β (Aβ) clearance from the brain to blood might play a key role in the development of Alzheimer's disease (AD). Aβ is normally bound to and transported by albumin in blood, thus possibly maintaining constant concentration of free Aβ in the blood. We therefore hypothesized that decreased blood levels of albumin‐Aβ complexes could be associated with decreased Aβ removal from the brain to blood, resulting in Aβ accumulation in the brain. Methods We carried out a cross‐sectional investigation of the association between serum levels of albumin‐Aβ complexes (SLAAC) and AD prevalence in 89 patients who visited our outpatient clinic, and gave written informed consent between August 2008 and May 2012. Results We confirmed 45 cases of AD. Low SLAAC was associated with an increased prevalence of AD (OR 0.27; 95% CI 0.14–0.51) in a univariable logistic model and multivariable logistic models. In addition, decreased SLAAC was associated with decreased levels of Aβ42 in CSF (r = 0.38, P = 0.0221) and increased levels of p‐tau in CSF (r = −0.43, P = 0.0090), findings that have been shown to be associated with AD progression. Conclusions This novel method might be very useful for monitoring of the progression of AD. Geriatr Gerontol Int 2014; 14: 716–723.